Ordinance no. 67: An Ordinance to Prohibit the Selling of Dangerous Weapons to Minors, in Morning Appeal, Apr. 18, 1885, at 1, § 1 - (:unkn) unknown (My University, 1885)
It shall be unlawful for any person, firm or association to sell or dispose of any dirk, dirk knife, sword, sword cane, billy, slung shot, revolver pistol, gun or other dangerous or deadly weapon, to any person under the age o 21 years.
Keywords: TRANSFER - MINORS